2019
DOI: 10.1128/jb.00205-19
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation as a Widespread Regulatory Mechanism in Prokaryotes

Abstract: Phosphorylation events modify bacterial and archaeal proteomes, imparting cells with rapid and reversible responses to specific environmental stimuli or niches. Phosphorylated proteins are generally modified at one or more serine, threonine, or tyrosine residues. Within the last ten years, increasing numbers of global phosphoproteomic surveys of prokaryote species have revealed an abundance of tyrosine-phosphorylated proteins. In some cases, novel phosphorylation-dependent regulatory paradigms for cell divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 86 publications
0
11
1
Order By: Relevance
“…Additionally, we found that Tyr153 but not Tyr152 is the major phosphorylation site on CesT being phosphorylated by NleH2. This is contradictory to the previous finding involving molecular dynamic simulations for CsrA with phosphorylated CesT (Tyr152), which indicated that competitive binding: PO 3 ‐mediated tripartite H‐bonding between CseT and CsrA at specific residues (Ser41, Val42, and His43) could compete with CsrA binding to the “GGA” motif on target mRNA 28 . However, it was shown that Y153F mutation leads to increased Non‐LEE encoded effector A (NleA) translation and secretion 27 .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Additionally, we found that Tyr153 but not Tyr152 is the major phosphorylation site on CesT being phosphorylated by NleH2. This is contradictory to the previous finding involving molecular dynamic simulations for CsrA with phosphorylated CesT (Tyr152), which indicated that competitive binding: PO 3 ‐mediated tripartite H‐bonding between CseT and CsrA at specific residues (Ser41, Val42, and His43) could compete with CsrA binding to the “GGA” motif on target mRNA 28 . However, it was shown that Y153F mutation leads to increased Non‐LEE encoded effector A (NleA) translation and secretion 27 .…”
Section: Discussioncontrasting
confidence: 98%
“…This is contradictory to the previous finding involving molecular dynamic simulations for CsrA with phosphorylated CesT (Tyr152), which indicated that competitive binding: PO 3 -mediated tripartite H-bonding between CseT and CsrA at specific residues (Ser41, Val42, and His43) could compete with CsrA binding to the "GGA" motif on target mRNA. 28 However, it was shown that Y153F mutation leads to increased Non-LEE encoded effector A (NleA) translation and secretion. 27 This suggested that differential phosphorylation of CesT at Tyr152 and Tyr153 by NleH2 might be involved in regulating the translation and secretion of another effector protein NleA.…”
Section: Discussionmentioning
confidence: 99%
“…Readers are proteins without enzymatic activity that bind to specific protein domains once they carry a PTM, and mediate the effect of the modification in different ways, such as establishing or preventing protein interactions, or inducing a translocation of subcellular localisation (Figure 1B). The concept of writers, readers and erasers for posttranslational modifications, as described in [33], is known for a range of different modifications, such as the histone code in the field of epigenetics [34,35], or phosphotyrosine binding domains [36,37]. Also in glycobiology, a large number of glycosyltransferases (writers) and glycoside hydrolases (erasers) are complemented by proteins specifically recognizing different types of glycosylation (readers) [38,39].…”
Section: Accepted Articlementioning
confidence: 99%
“…The phosphorylated tyrosine residue in EI, Tyr122, is a conserved residue between EI sugar and EI Ntr (33), suggestive of its importance. Notably, extensive tyrosine phosphorylation occurs in proteins linked to sugar metabolism and the TCA cycle in E. coli and in the archaeon Sulfolobus solfataricus (55), suggesting that the impact of tyrosine phosphorylation on proteins that function in carbohydrate metabolism is conserved through evolution. The finding that tyrosine phosphorylation regulates the activity of the catabolite regulator Cra (22), together with our findings that it regulates localization of EI and of the factor that controls EI activity, TmaR, supports this hypothesis.…”
Section: Coli Encounters Does Tmar Absence Confer a Disadvantage?mentioning
confidence: 99%